2001
DOI: 10.1677/joe.0.1710541
|View full text |Cite
|
Sign up to set email alerts
|

The vasorelaxant hormone relaxin induces changes in liver sinusoid microcirculation: a morphologic study in the rat

Abstract: This study shows that specialized contractile endothelial cells exist in rat liver sinusoids which may be involved in the local control of hemodynamics and which are sensitive to vasoactive agents, including the vasorelaxant hormone relaxin. Male rats were treated with 10 µg relaxin for 4 days; phosphate-buffered saline (PBS)-treated rats were the controls. For comparison, rats treated with relaxin together with the NO-synthase inhibitor N -nitro--arginine methyl ester (L-NAME), and rats treated with the vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Interestingly, effects of relaxin have been detected in normal (undiseased) liver. Porcine relaxin treatment caused morphological changes in rat perisinusoidal liver cells, and dilation of the sinusoids [14]. Relaxin had protective effects against ischemia and reperfusion damage in perfused rat liver [37].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, effects of relaxin have been detected in normal (undiseased) liver. Porcine relaxin treatment caused morphological changes in rat perisinusoidal liver cells, and dilation of the sinusoids [14]. Relaxin had protective effects against ischemia and reperfusion damage in perfused rat liver [37].…”
Section: Discussionmentioning
confidence: 92%
“…Relaxin treatment of rats caused acute changes in hepatic microcirculation, and induced morphological changes in sinusoidal myofibroblastic cells [14]. In addition, the relaxin-null mouse developed significantly increased liver weight [15], although it was not reported if this phenomenon was due to increased collagen.…”
Section: Insl3mentioning
confidence: 99%
“…Studies have also shown that Rlx has a potent effect on the vasculature of the liver [15] and lung [16]. In the kidney, Rlx increases renal blood flow without an effect on systemic blood pressure [2].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, pRLX dilated the liver sinusoids. This effect was reduced by NO synthesis inhibition, suggesting a role for NO (6).…”
Section: Influence Of Rlx On the Vasculature Of Other Organsmentioning
confidence: 91%